The role of double-loop learning in manufacturing supply chains. The study of the disruptions driven by COVID-19 in Poland - Frankowska, Marzena; Swierczek, Artur; Cheba, Katarzyna (Technological and Economic Development of Economy, 2023)
A global pandemic of coronavirus COVID-19 affects the manufacturing supply chains significantly. This study aims to identify and evaluate the reaction of manufacturing supply chains in using the concept of double-loop learning to mitigate the disruptions induced by COVID-19 at the early stage of pandemic. A two-stage research process has been developed that firstly involves determining the learning pattern of enterprises in industrial supply chains and identifying actions taken. Then, the relationship between taking actions in the field of double-loop learning in the manufacturing supply chains and expecting a change in their market situation, and having knowledge in the field of adaptation to changes caused by the COVID-19 pandemic was examined. The study shows that there is a high level of caution in taking proactive measures in supply chains and a lack of knowledge in the field of adapting industrial supply chains to sudden disruptions caused by the COVID-19 pandemic. First published online 01 December 2022